Topological graph polynomials in colored Group Field Theory - Gurǎu, Rǎzvan (Annales Henri Poincaré, 2010)
In this paper, we analyze the open Feynman graphs of the Colored Group Field Theory introduced in Gurau (Colored group field theory, arXiv:0907.2582 [hep-th]). We define the boundary graph $${\mathcal{G}_{\partial}}$$of an open graph $${\mathcal{G}}$$and prove it is a cellular complex. Using this structure we generalize the topological (Bollobás-Riordan) Tutte polynomials associated to (ribbon) graphs to topological polynomials adapted to Colored Group Field Theory graphs in arbitrary dimension.